Round scad quality on mini purse seine boats, Rembang Regency, Central of Java - Rejeki, Sri Untari Puji; Darmanto, Y.S.; Dewi, Eko Nurcahya; Mulyandari, Nunik; Darmawan, Darmawan; Himam, M. Iqbal; Nazaruddin, Nazaruddin; Syahputra, Jasnur (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Mini purse seine boats in Rembang are divided into two sizes. The first one, namely mini purse seines measuring 10 - 20 Goss Tonnage (GT) (short trips) with a fishing operation duration of 3 - 7 days. The second one is mini purse seines measuring 21 - 30 GT (long trips) with a fishing operation duration of 7 - 10 days. The dominant catch on this boats is round scad, which used a cooling mechanism with ice blocks and bulking systems. This research evaluates the quality of round scad caught by mini purse seine boats (based on Indonesian National Standard/SNI 2729: 2013) and the quality of ice used in handling the fish (based on SNI 4872: 2015). The sampling technique was purposive sampling. Fish samples were carried out in the first and last hold on the short trips and long trips boats, where each handle of the fish was sampled in the upper, middle, and lower layers. Data analysis for sensory evaluation were analyzed by Kruskal Wallis statistics, while the TPC value of round scad was tested by ANOVA test. The laboratory test results obtained the sensory assessment of round scad. The value of the TPC round scad and the E. coli ice blocks are still within the limits of the Indonesian national standards, but the TPC scale of the ice block exceeds the standard limit of SNI. The Kruskal Wallis statistics results showed tha the difference in fish hold, the difference in the trip, and differences in fish hold layers had a significant effect on the sensory of scad. ANOVA test showed that differences in the fish hold and trip differences had a significant impact on the TPC of scad. In contrast, the difference in fish hold layers gave a non-significant effect on the TPC of round scad.Keywords:Quality organolepticTPcRound scadMini purse seineRembang